Surgical Management of Complications after Dexamethasone Implant - Giancarlo Sborgia; Alfredo Niro; Francesco D’Oria; Alessandra Galeone; Luigi Sborgia; Francesco Boscia; Alessandra Sborgia; Giovanni Alessio (Case Reports in Ophthalmological Medicine)
Purpose. To report surgical management of ocular complications occurred after dexamethasone (DEX) implant (Ozurdex®) injection. Methods. Retrospective interventional case series. Results. Different surgical procedures including viscoexpression to manage the migration of the implant into the anterior chamber, “phaco-rolling” technique for the intralenticular injection, and vitrectomy with implant removal for an acute endophthalmitis were performed. Successful management of different complications after DEX implant by using individualized surgical approaches was observed. Conclusions. Early and targeted surgical management is required in selected cases of ocular complications after DEX implant. The implant removal was needed to preserve ocular anatomy and function.